THE EFFECT OF FOOTBALL CLEATS STUDS DESIGN TO AMATEUR FOOTBALL PLAYER PERFORMANCE EVALUATION - Muslim, Erlinda; Brahmantyo, Bagas; Utami, Fristya Fadhilah; Jasmine, Virozza Bianca (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
Football is the world's number one sport in terms of popularity and technology development. The football competition has an amateur football player that aims to find the hidden talents in football game. Therefore, investing for research in technology and environment to find the best performance in amateur football for the results of the test. Some adjustments have been made with emerging technologies, one of the most visible change is the shoes with different design types. The invention is used to identify and evaluate what different teams need in different positions. In this study, the performance principles undertaken by ergonomics in sports and performance by trainers, the results obtained are the most appropriate forms of shoes that used well in the field of synthetic grass. The research will be given the analysis of shoes per level and position and will be check by the Key Performance Index provided by the trainer.Â